2022
DOI: 10.1002/admi.202201797
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Poly(Ionic Liquid) Nanomembranes for High Performance Mg2+/Li+ Separation

Abstract: The fragility and brittleness of glassy poly(ionic liquid)s (PILs) hinders the processing of ultrathin PILs membranes. This work is reported the interfacial polymerization of PILs, which enables the first preparation of defect‐free PIL nanomembranes for high flux separation of lithium (Li+, 3.8 Å) and magnesium (Mg2+, 4.3 Å) ions mixture. Aqueous solution of an amine‐functionalized PIL is brought in contact with trimesoyl chloride (TMC) hexane solution. The “amine ≈ acyl chloride” condensation reaction occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Lastly, in most cases, the IL is used as an additive. 48,49 2.1.2 Bio-based solvents. Ong et al 21 used decanoic acid in the IP organic phase, which is a medium chain fatty acid found in coconut oil, palm kernel oil, and animal fats.…”
Section: 'Green' Solventsmentioning
confidence: 99%
“…Lastly, in most cases, the IL is used as an additive. 48,49 2.1.2 Bio-based solvents. Ong et al 21 used decanoic acid in the IP organic phase, which is a medium chain fatty acid found in coconut oil, palm kernel oil, and animal fats.…”
Section: 'Green' Solventsmentioning
confidence: 99%
“…For example, Ni et al found that the long chain nature of PILNH 2 polymers contributed to the stable microstructures in PILNH 2 -TMC nanomembranes with stable flux versus pressure. 151 In their study, Chen et al analyzed how the different amounts of [EMIM][B(CN) 4 ] impacted the mechanical properties of ILPMs made with PVDF. They found that as the IL content increased, the Young's modulus, tensile strength, and extension at break decreased.…”
Section: Stabilitymentioning
confidence: 99%
“…Apart from PEI and PIP as aqueous monomers, researchers [ 18 , 19 ] have also used other chemicals as monomers during interfacial polymerization. For example, recently, Peng et al [ 18 ] synthesized a quaternized-spiral piperazine (QSPIP) featuring a spiral conformation and quaternary/secondary amines and used it as an aqueous monomer to react with TMC via interfacial polymerization and fabricated a kind of QSPIP-TMC membrane, which achieved an approximately five-times-improved water permeance (220 LMH/MPa) compared with analogous polyamide membranes and a good Mg/Li selectivity of 8.7.…”
Section: Introductionmentioning
confidence: 99%